Emergence of plasmid-mediated multidrug resistance in epidemic and non-epidemic strains of Salmonella enterica serotype Typhi from Jordan - Al-Sanouri, Tarek M.; Paglietti, Bianca; Haddadin, Aktham; Murgia, Manuela; Bacciu, Donatella; Youssef, Mahammad; Rubino, Salvatore (The Journal of Infection in Developing Countries, 2008)
Background: Enteric fever caused by Salmonella enterica serovar Typhi has not been adequately explored in Jordan.Methodology: In this study we investigated antibiotic resistance patterns and resistance determinants coupled with fingerprint methods of forty-eight isolates of S. Typhi obtained from 113 patients with suspected enteric fever admitted at six governmental hospitals in different directorates in Jordan. Twenty-four isolates were from an outbreak of typhoid fever that occurred between October 2004 and January 2005, and another twenty-four were from sporadic cases from 2005.Results: All isolates of S. Typhi were resistant to streptomycin. A multidrug resistant (MDR) pattern of ampicillin, chloramphenicol, co-trimoxazole with tetracycline and streptomycin (R-type ACCoTS) was found in 58% of the epidemic strains causing the outbreak and in 98% of the strains from sporadic cases. MDR isolates harbored a single IncHI1 plasmid containing a class 1 integron (dfrA7). Plasmid conjugation studies demonstrated a genetic transfer of resistance (ACCoT). S. Typhi isolates were all sensitive to fluoroquinolones and cefotaxime, the alternative drugs recommended for treatment of typhoid fever. The genomic analysis using PFGE showed: a) the outbreak was caused by an introduced circulating clone with/without an MDR plasmid, and b) isolates from the sporadic cases from 2005 are the same MDR clone that persisted and spread in the country.Conclusion: The emergence of MDR S. Typhi strains is a majorn important public health issue in Jordan. This study should guide selection of effective antibiotic therapy for the treatment of typhoid and monitoring of the spread of MDR of S. Typhi.